Estudio de propuesta para el equipamiento y uso del laboratorio de electrónica de potencia del AEIRNNR de la Universidad Nacional de Loja. - Espinoza Toledo, Mariela Rocío (2015)
Actually Ecuador is thronging a process of accreditation of educational institutions of higher level that are providing services in the Ecuadorian territory, the CEAACES is uncharged of this function (Council of Evaluation, Accreditation and Quality Assurance Higher Education), so it is necessary to regulate the way they have been taking the practical activities carried out in the Electronics Laboratory. The present project a practical plan for the Electronics Laboratory, the subjects that are part of the project are: Electronics Practice I, Power Electronics and Microcontrollers based on the topics described in the syllabus of the subjects that form part of the investigation, according with the information obtained we suggest a list of equipment that could be considered for extension of this laboratory, so important into normative to the good use and handling of equipment and installations.